THE EFFECT OF KNOWLEDGE ABOUT COOPERATIVES, COOPERATIVE MOTIVATION AND SERVICE QUALITY ON INTEREST TO BECOME KOPPONTREN MEMBERS - Eki Wijayanti; Agung Guritno; Abdul Aziz Nugraha Pratama (Jurnal Ekonomi, 2023)
The purpose of this study was to determine the effect of knowledge about cooperatives, cooperative motivation and quality of service on interest in becoming a member of the Al Falah Koppontren. This study uses a quantitative method by processing primary data with a questionnaire given to students of the Al-Falah Islamic boarding school as many as 150 respondents, using a stratified random sampling technique. The data obtained were processed with IBM SPSS Statistics 23. The analysis used in this study was carried out using instrument tests, classical assumption tests, regression analysis and statistical tests. Based on the research results, it can be seen that cooperative knowledge, cooperative motivation and service quality have a significant positive effect on the intention to become a member of a cooperative.